2006
DOI: 10.1038/sj.cgt.7700950
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for prophylactic cancer vaccines and need for a paradigm shift

Abstract: This review summarizes clinical experience with infectious disease vaccines and data from animal tumor models that support a paradigm shift for cancer vaccines from therapeutic to prevention applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Clinical examination and routine blood checks were performed at every visit (weeks 1,2,4,6,8,10,12,14,18,22,24). Patients were assessed for signs of autoimmune disease by measurement of thyroid hormones and pancreatic enzymes, screening for anti-nuclear antibodies as well as monitoring of rheumatoid factor and complement factors.…”
Section: Clinical Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examination and routine blood checks were performed at every visit (weeks 1,2,4,6,8,10,12,14,18,22,24). Patients were assessed for signs of autoimmune disease by measurement of thyroid hormones and pancreatic enzymes, screening for anti-nuclear antibodies as well as monitoring of rheumatoid factor and complement factors.…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…[1][2][3] However, tumor vaccination may be appropriate in a more favourable setting, such as minimal residual disease after surgery or successful systemic therapy. 4 Therefore, clinical development of vaccines remains a potentially useful experimental approach. In clinical trials, the most widely used vaccines were antigenic peptides/proteins plus adjuvant or cellular vaccines, such as antigen-loaded dendritic cells or modified tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, this differential efficacy of the cancer vaccine in prophylaxis and therapy has been proven by several other studies evaluating the feasibility of a cancer vaccine with tolerized tumor antigens. [42][43][44][45][46] Novakovic et al 44 found that the proportion of protected mice was 75-100% by vaccination of irradiated melanoma tumor cells with CpG ODN in a prophylactic setting whereas the rates of cured mice were only 11.1-21.1% in a therapeutic setting. Garcia-Hernandez Mde et al 45 recently reported that prophylactic vaccination with a prostate antigen, six-transmembrane epithelial antigen of prostate, significantly delayed tumor growth and improved survival whereas therapeutic vaccination induced a modest delay in the growth of established prostate tumors.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%
“…22 We chose a prophylactic tumor vaccination model since therapeutic vaccination has been largely disappointing during the past decades, whereas vaccines able to induce protective immunity in the situation of minimal residual disease are possibly more appropriate for clinical application. 23 In this study, we asked (1) whether the adjuvant activity of CCL19 can also be observed after intradermal gene gun delivery of DNA, (2) which application route (intramuscular or intradermal) should be preferred for the further preclinical development of a Her2/neu-CCL19 DNA vaccine and (3) which role can be attributed to B cells (which may also express CCR7) in our system.…”
Section: Introductionmentioning
confidence: 99%